Pregnant Women's Satisfaction with The Quality of Antenatal Care (Anc) Services at The Obstech Of Poly of UPT Nene Mallomo Hospital, Sidrap District - Dian Meiliani Yulis; Hairuddin K Hairuddin K; Andi Alim; Serli Serli (Universitas of Muhammadiyah Makassar, 2023)
In Indonesia, the quality of ANC services is still low in terms of ANC coverage which is still below the national target where data on coverage of pregnant women (K4) visits in Indonesia in 2021 is 87.48%, which means that it has not reached the target of the Ministry of Health's Strategic Plan in 2021, which is 95 %. Of the 34 provinces in Indonesia, only 3 provinces have achieved this target, namely the Riau Islands, DKI Jakarta and West Java. The purpose of this study was to know the relationship between the quality of antenatal care (ANC) services and the level of satisfaction of pregnant women at the midwifery polyclinic of UPT RSUD Nene Mallomo. The research design method used an analytic survey research with a cross-sectional approach, the number of samples was 83. The research instrument used a questionnaire, bivariate analysis used the Chi Square test. Results Based on data from 83 pregnant women who were dissatisfied with ANC services as many as 15 people (18.1%), based on Tangibles not good and dissatisfied 16 (19.3%), Empathy 16 (19.3%) The conclusion is that there is a relationship between satisfaction with Tangibles (P-value=0.000 OR 140.80), Reliability (P-value=0.000 OR 86.66), Responsiveness (P-value=0.000 OR 303.3), Assurance (P-value=0.000 OR 140.8 ) and Empathy (P-value = 0.000 OR 140.8) It is suggested that health workers improve counseling for pregnant women to make regular ANC visits.